2020
DOI: 10.3390/s20185165
|View full text |Cite
|
Sign up to set email alerts
|

Hardware Trojans in Chips: A Survey for Detection and Prevention

Abstract: Diverse and wide-range applications of integrated circuits (ICs) and the development of Cyber Physical System (CPS), more and more third-party manufacturers are involved in the manufacturing of ICs. Unfortunately, like software, hardware can also be subjected to malicious attacks. Untrusted outsourced manufacturing tools and intellectual property (IP) cores may bring enormous risks from highly integrated. Attributed to this manufacturing model, the malicious circuits (known as Hardware Trojans, HTs) can be imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 166 publications
(217 reference statements)
0
20
0
Order By: Relevance
“…In addition to common physical and electrical inspection methods along with counterfeit avoidance measures to detect these counterfeit components proactively, rather than reactive manner after an attack. Dong et al 71 surveyed the state of the art for HTs, demonstrating threats, and the methods for preventing and detecting hardware Trojans.…”
Section: Hardware Trojanmentioning
confidence: 99%
“…In addition to common physical and electrical inspection methods along with counterfeit avoidance measures to detect these counterfeit components proactively, rather than reactive manner after an attack. Dong et al 71 surveyed the state of the art for HTs, demonstrating threats, and the methods for preventing and detecting hardware Trojans.…”
Section: Hardware Trojanmentioning
confidence: 99%
“…To implement the malicious behaviors, attack technologies can be wireless signal hijacking inerfering, hardware Trojans [102], malware, side channel analysis [97], SQL injection, attack on the sensors and APs [97], poisoning attack for machine learning, adversarial attack with adversarial example, oracle attack, membership inference attack, and reverse engineering [96], to name a few.…”
Section: Cyber Security In Smart Factorymentioning
confidence: 99%
“…The hardware security and trust research community has been focused on developing effective detection mechanisms to uncover different kinds of HTs during the design and manufacturing processes of ICs. Among the tools that can detect HTs in pre-silicon phase stand out the COTD tool, VeriTrust, FANCI or the recently published HTDet tool [1]. These tools have proven to be effective against the HTs contained in widespread HT benchmarks.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, researchers have also shown that some of these schemes can be circumvented [2]. Among the post-fabrication detection methods stand out those based on side-channel analysis or logic testing [1]. Finally, different prevention methods have been developed during the last decade.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation